2017
DOI: 10.1080/17405629.2017.1367278
|View full text |Cite|
|
Sign up to set email alerts
|

Citizenship’s tangled web: Associations, gaps and tensions in formulations of European youth active citizenship across disciplines

Abstract: How does academic literature across various disciplines conceptualize and empirically address active citizenship? What are the potential benefits and dangers of dominant epistemological and ideological perspectives on 'good citizenship'? Our paper engages with these questions by drawing on literature across 8 disciplines. We used textual analysis software T-LAB to quantify and visualize co-occurrences, word associations and thematic clusters in the abstracts of 770 texts gathered by eight country teams and ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…It is fundamental to address the problems of distrust towards political institutions and of lack of subjective personal agency regarding political issues. The neglect of the youth's political ownership, which continues to emerge both in socio-political (Pontes et al, 2018) and academic narratives (Banaji, et al, 2018), needs to be tackled.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…It is fundamental to address the problems of distrust towards political institutions and of lack of subjective personal agency regarding political issues. The neglect of the youth's political ownership, which continues to emerge both in socio-political (Pontes et al, 2018) and academic narratives (Banaji, et al, 2018), needs to be tackled.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…As Milana (2008) put it, the notion of European active citizenship is used to legitimize the EU rather than to include diverse groups of citizens. Similarly, in their systematic meta-review of youth citizenship in the existing literature of social sciences, Banaji et al (2018) concluded that most key-terms may be inclusive of Europe in their theory and research, but they are not explicit of or specifically conceived around Europe.…”
Section: Discussionmentioning
confidence: 99%
“…In his seminal work, Politics, the Greek philosopher Aristotle depicted what today constitutes a normative view of the good citizen with rights and responsibilities, tightly connected to the ideal democratic city-state, with justice acting as a fundamental moral framework (cf. Banaji et al, 2018). More recently, a number of scholars have pointed out that this mainstream view of the 'good citizen' is ideologically bound and far from inclusive.…”
Section: Civic Engagement and Political Participationmentioning
confidence: 99%
“…4, 27;Abowitz & Harnish, 2006. p. 671;Hoskins et al, 2015, p. 434). Nevertheless, it must be noted that considering the findings of studies conducted by Banaji et al (2018), it is hard to expect that school education will have the features of the critical concept of citizenship.…”
Section: The Concepts Of Citizenshipmentioning
confidence: 99%